Transient Peripheral Carotid Inflammation Syndrome Diagnosed by Contrast-enhanced Ultrasound: A Case Report - PAN Chunlei; WANG Ying; WANG Yahong; ZHANG Li; GE Zhitong; CHEN Yu; CAI Sheng; WANG Hongyan; YANG Xiao; LI Jianchu (Xiehe Yixue Zazhi)
Transient perivascular inflammation of the carotid artery (TIPIC) syndrome is a relatively rare disease, and ultrasound is the first screening method for initial diagnosis of the disease. Contrast-enhanced ultrasound (CEUS) has unique advantages in the follow-up of patients with TIPIC syndrome. This paper reports a patient with TIPIC syndrome who was treated with acute left neck pain. The inflammation was significantly relieved and subsided after treatment with non-steroidal anti-inflammatory drugs. The ultrasound changes of carotid artery lesions in this patient during follow-up were analyzed, and the application value of CEUS in the follow-up diagnosis of this disease was summarized, in the hope of providing clinical reference.